MADRASAH QUALITY CULTURE DEVELOPMENT PATTERNS AT MA MA'ARIF NU 1 KEMRANJEN BANYUMAS INDONESIA - Ernawati; Abdul Basit, (International Journal of Scientific Research and Management (IJSRM), 2021)
This research was conducted to determine the characteristics and management patterns of the quality development of madrasa culture in Madrasah Aliyah Ma'arif NU 1 Sirau  Kemranjen Banyumas Indonesia. This study uses a mixed approach (qualitative-quantitative), but is categorized as a case study because it cannot be generalized. The object of the research is the madrasa culture at Madrasah Aliyah Ma'arif NU 1 Sirau  Kemranjen Banyumas holistically covering all madrasa residents and their interactions. The research data were collected by means of observation, questionnaires and documentation. The results show that, first,  the characteristics of the madrasa culture consist of a madrasa atmosphere, a culture of cooperation, a culture of discipline, a culture of reading, a clean culture, physically and mentally healthy, a culture of religious, polite and civilized behavior in a positive condition. Second, Madrasah development management is carried out in such a way as to produce better character changes. Keywords: Madrasa culture, management, characteristics.